PENGARUH SABANG HERITAGE SOCIETY TERHADAP EKSISTENSI SITUS BUDAYA DI KOTA SABANG, 2008-2017 - Kamelia Hannani; Mawardi .; Zainal Abidin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACTThe research entitled "The Influence of Sabang Heritage Society to the Existence of Cultural Site in Sabang City, 2008-2017", aims to (1) explain the background of Sabang Heritage Society, (2) explain what activities conducted by Sabang Heritage Society since 2008 (3) analyzed the influence of Sabang Heritage Society towards the existence of cultural sites in Sabang City, 2008-2017 and (4) explained the support of the government and community of Sabang City towards Sabang Heritage Society, 2008-2017. This research uses qualitative approach and historical method, which has the step of theme selection, heuristic, verification, interpretation and historiography. Technique of collecting data is done by interview, documentation, observation and literature study. Based on the results of the research, it is known that (1) Sabang Heritage Society was established in 2007 and was notarized in 2008 based on the awareness of the intellectuals, it will be important to preserve the historical heritage that has been abandoned and has not been maximized by the empowerment and the need for excavation of cultural heritage sites in Sabang City, (2) Since 2008-2017 the Sabang Heritage Society has held various activities such as: Dutch Colonial asset investment, Sabang City history training and seminar, documentation video creation cooperation, construction of Sabang airline complex 1909, construction of object / location inscription historic, held Sabang Expo and Sabang Regatta Expo, making video documentation "Acrhipelogo program, Metro TV", making video documentation Metro File Program, Metro TV, construction of Kherkof European grave gates, excavation bunker Japan hill overpass, Revitalization of Anoi Castle, Sabang Regatta Expo, ( 3) Government and community support in the form of funding, facilities, facilities and infrastructure and welfare to Sabang Heritage Society employees. In addition to government support the existence of the Sabang Heritage Society also received support from the community by engaging in various activities undertaken by the Sabang Heritage Society. Keywords: Influence, Sabang Heritage Society, Existence of Cultural Site, Sabang City.  ABSTRAKPenelitian yang berjudul “Pengaruh Sabang Heritage Society Terhadap Eksistensi Situs Budaya di Kota Sabang, 2008-2017”, bertujuan untuk (1) menjelaskan latar belakang dibentuknya Sabang Heritage Society, (2) menjelaskan apa saja kegiatan yang dilakukan oleh Sabang Heritage Societysejak tahun 2008-2017, (3) menganalisis pengaruh Sabang Heritage Society terhadap eksistensi situs budaya di Kota Sabang, 2008-2017 dan (4) menjelaskan dukungan pemerintah dan masyarakat Kota Sabang terhadap Sabang Heritage Society, 2008-2017.Penelitian ini menggunakan pendekatan kualitatif dan metode sejarah, yang memiliki langkah pemilihan tema, heuristik, verifikasi, interpretasi dan historiografi. Teknik pengumpulan data dilakukan dengan wawancara, dokumentasi, observasi dan studi pustaka.Berdasarkan hasil penelitian diketahui bahwa (1) SabangHeritage Society berdiri tahun 2007 dan dinotariskan tahun 2008 yangdilatarbelakangi oleh kesadaran para cendikiawan akan pentingkanya melestarikan warisan sejarah yang telah banyak terbengkalai dan belum maksimal dilakukan pemberdayaan serta perlu diadakannya penggalian terhadap situs-situs cagar budaya yang terdapat di Kota Sabang, (2) Sejak 2008-2017 Sabang Heritage Society telah mengadakan berbagai kegiatan seperti: investasi aset Kolonial Belanda, pelatihan dan seminar sejarah Kota Sabang, kerja sama pembuatan video dokumentasi, pembangunan gerbang komplek Sabang Maskapai 1909, pembangunan prasasti objek/lokasi bersejarah, mengadakan Sabang Expo dan Sabang Regatta Expo, pembuatan video dokumentasi “program Acrhipelogo, Metro TV”, pembuatan video dokumentasi Program Metro File, Metro TV, pembangunan gerbang Kherkof makam Eropa, penggalian bunker Jepang bukit layang, Revalisasi Benteng Anoi, kegiatan Sabang Regatta Expo, (3) Dukungan pemerintah dan masyarakat berupa pendanaan, fasilitas, sarana dan prasarana dan pemberian kesejahteraan kepada karyawan Sabang Heritage Society. Selain dukungan pemerintah keberadaan Sabang Heritage Society juga mendapat dukungan dari masyarakat dengan mengikutsertakan dalam berbagai aktifitas yang dilakukan oleh Sabang Heritage Society. Kata Kunci: Pengaruh, Sabang Heritage Society,Eksistensi Situs Budaya, Kota Sabang